YAP9/A20 complex suppresses proinflammatory responses and provides novel anti-inflammatory therapeutic potentials - Yang, Fengyuan Mandy; Shen, Liya; Fan, Dengxia Denise; Bai, Yaqin; Li, Bizhou; Lee, Jongdae (Frontiers in Immunology, 2022)
Innate anti-inflammatory mechanisms are essential for immune homeostasis and can present opportunities to intervene inflammatory diseases. In this report, we found that YAP isoform 9 (YAP9) is an essential negative regulator of the potent inflammatory stimuli such as TNFα, IL-1β, and LPS. YAP9 constitutively interacts with another anti-inflammatory regulator A20 (TNFAIP3) to suppress inflammatory responses, but A20 and YAP can function only in the presence of the other. YAP9 uses a short stretch of amino acids in the proline-rich domain (PRD) and transactivation domain (TAD) suppress the inflammatory signaling while A20 mainly uses the zinc finger domain 7 (ZF7). Cell-penetrating synthetic PRD, TAD, and ZF7 peptides act as YAP9 and A20 mimetics respectively to suppress the proinflammatory responses at the cellular level and in mice. Our data uncover a novel anti-inflammatory axis and anti-inflammatory agents that can be developed to treat acute or chronic conditions where TNFα, IL-1β, or LPS plays a key role in initiating and/or perpetuating inflammation.